Dysregulation of lipids in Alzheimer's disease and their role as potential biomarkers. Issue 7 (24th February 2017) - Wong, Matthew W.; Braidy, Nady; Poljak, Anne; Pickford, Russell; Thambisetty, Madhav; Sachdev, Perminder S.
Abstract: The brain is highly enriched in lipids, and an intensive study of these lipids may be informative, not only of normal brain function but also of changes with age and in disease. In recent years, the development of highly sensitive mass spectrometry platforms and other high‐throughput technologies has enabled the discovery of complex changes in the entire lipidome. This lipidomics approach promises to be a particularly useful tool for identifying diagnostic biomarkers for early detection of age‐related neurodegenerative disease, such as Alzheimer's disease (AD), which has till recently been limited to protein‐ and gene‐centric approaches. This review highlights known lipid changes affecting the AD brain and presents an update on the progress of lipid biomarker research in AD. Important considerations for designing large‐scale lipidomics experiments are discussed to help standardize findings across different laboratories, as well as challenges associated with moving toward clinical application.